New trends in the ovarian cancer treatment - Marczak, Agnieszka; Bukowska, Barbara (Menopause Review/Przegląd Menopauzalny, 2013)
Ovarian cancer is the fifth most lethal malignancy in women. The standard treatment of this disease is chemotherapy which is, however, often inefficient. The failure of chemotherapy is due to the developing multidrug resistance and the presence of cancer stem cells. This article describes research on new drugs, which can overcome these limitations. Some of the substances which are effective in cancer cells resistant to the standard approach are bisintercalating anthracyclines and epothilones. One of the bisanthracyclines is WP 631, which is more effective than commonly used first-generation anthracyclines, even on cells resistant to cisplatin or doxorubicin. In turn, epothilones have a similar mechanism of action as taxanes. They stabilize microtubules and consequently perturb mitosis. Both WP 631 and epothilones appear to be hopeful candidates to break multidrug resistance because of their low affinity for P-glycoprotein – the efflux pump for drugs. Substances, which effectively eliminate cancer stem cells include metformin, Müllerian inhibiting substance, and salinomycin. Metformin has a proapoptotic activity and exhibits synergism with cisplatin – a chemotherapeutic agent used in ovarian cancer treatment. Müllerian inhibiting substance perturbs the cell cycle, while salinomycin inhibits proliferation and induces apoptosis in the ovarian cancer cells. The search for new drugs effective in the ovarian cancer treatment, especially in cases resistant to current forms of therapy, remains a challenging priority.